Transient adaptation and sensitization in the retina of Necturus (The Rockefeller University Press, 1980)
Responses to repetitive stimulation were monitored at several retinal levels in the eyecup of the mudpuppy Necturus maculosus. When alternating sequences of low-intensity small and large spots were presented, two effects were found, which could be localized to the proximal retina: (a) response decrement (RD), in which, after the first small spot response, subsequent small spot responses are decreased in amplitude and (b) transient response enhancement (TRE), in which the first small spot response after a large spot sequence is larger than preceding or subsequent small spot responses. RD and TRE are absent or weak in sustained on or off responses (horizontal and bipolar cells, and ON and OFF ganglion cell post-stimulus time histograms (PSTH) but are particularly well developed in the on/off responses of the proximal retina (proximal negative response, M-wave, PSTHs of ON/OFF ganglion cells, and intracellular responses from on/off neurons and Muller cells). RD and TRE appear to arise from a stimulus-evoked slow depolarization in on/off neurons that interacts with the amplitude of succeeding responses. We conclude that RD and TRE are a form of neural adaptation that is largely specific to the on/off channels of the proximal retina.